Rice--a step toward use of allelopathy - Olofsdotter, Maria (Wiley, 2001)
Rice (Oryza sativa L.) allelopathy has been on the research agenda for a decade. Now it is important to step back and look at its progress to enable priority setting for future research. This paper aims to do so primarily using the following five‐step protocol for allelopathy research: (i) carrying out laboratory, greenhouse, and field studies to illustrate the effect of released allelochemicals; (ii) isolating, identifying, and characterizing allelochemicals; (iii) establishing a correlation between growth inhibition and allelochemicals; (iv) performing genetic mapping of quantitative trait loci (QTLs) correlated with allelopathy; and (v) breeding for allelopathic cultivars tested for competitive ability in greenhouse and field experiments. Recent research on rice allelopathy has resulted in the following research milestones: There is large variation in allelopathy among rice cultivars.Allelopathy plays a role under field conditions.Allelopathic rice can suppress both mono‐ and dicot weed species.Progress has been made in identifying rice allelochemicals.Quantitative trait loci correlated with allelopathy have been identified.There is large variation in allelopathy among rice cultivars.Allelopathy plays a role under field conditions.Allelopathic rice can suppress both mono‐ and dicot weed species.Progress has been made in identifying rice allelochemicals.Quantitative trait loci correlated with allelopathy have been identified.This paper discusses the progress made in recent years and suggests some direction for future research.